Multiple Mechanisms of Shenqi Pill in Treating Nonalcoholic Fatty Liver Disease Based on Network Pharmacology and Molecular Docking. (26th June 2022) - Tong, Xiaojuan; Xu, Sumei; Zhai, Dong
Abstract : Background . Shenqi pill (SQP), a traditional Chinese prescription, has proven to be effective in treating nonalcoholic fatty liver disease (NAFLD). However, its bioactive ingredients and underlying mechanisms remain elusive. Aim . We aimed to predict the active compounds, potential targets, and molecular mechanisms of SQP anti-NAFLD by applying network pharmacology and molecular docking methods. Methods . Active ingredients and related targets of SQP were obtained from the TCMSP database. Potential targets of NAFLD were acquired from OMIM and GeneCards databases. The STRING database and Cytoscape software analyzed the protein-protein interaction (PPI) network and core targets of overlapping genes between SQP and NAFLD. GO enrichment analysis and KEGG enrichment analysis were performed in the DAVID database. Finally, molecular docking was employed to find possible binding conformations of macromolecular targets. Results . 15 anti-NAFLD bioactive ingredients and 99 anti-NAFLD potential targets of SQP were determined using Network pharmacology. Quercetin, kaempferol, stigmasterol, diosgenin, and tetrahydroalstonine were the major active ingredients and AKT1, TNF, MAPK8, IL-6, and VEGFA were the key target proteins against NAFLD. The KEGG analysis suggested that the main pathways included PI3K/Akt signaling pathway, HIF-1 signaling pathway, MAPK signaling pathway, and TNF signaling pathway. Molecular docking predicted that quercetin, kaempferol, stigmasterol, diosgenin, and tetrahydroalstonine could bind with AKT1, TNF, and MAPK8. Conclusion . This study successfully predicts the active compounds, potential targets, and signaling pathways of SQP against NAFLD. Moreover, this study contributed to the application and development of SQP.